Manufactured Factual Indeterminacy and the Globalisation of Tax Jurisprudence - Bret Bogenschneider (UCL Journal of Law and Jurisprudence, 2015)
In this article the ‘manufactured’ factual indeterminacy now ubiquitous within the practice of international taxation is presented as a result of intersecting global approaches to the theory of law. It is argued that tax law practice assumes a mixture of the theoretical positions averred by Hans Kelsen, Karl Llewellyn, and Ronald Dworkin. To combat the problems raised by this, a ‘Soft Realism’ approach is proposed in the application of tax heuristics to deal with cases of factual indeterminacy. Drawing some implications from this analysis, the debate over general anti-avoidance rules and complex tax avoidance strategies (eg ‘treaty-shopping’ and ‘double non-taxation’) is oriented within the overall framework of tax jurisprudence. Finally, it is argued that the globalisation of tax jurisprudence has enabled accounting firms to actively spread manufactured factual indeterminacy around the world, corrupting the purpose of the law in part by exploiting the weaknesses of formalistic legal interpretation. NB: the full text is available here: http://discovery.ucl.ac.uk/1472296/
Keywords: Dworkin; Kelsen; Tax jurisprudence